ANALISIS PENGARUH EXTERNAL HUMIDIFIER TERHADAP KINERJA OPEN CATHODE PROTON EXCHANGE MEMBRANE FUEL CELL - Adrio Irfan Fauzi; Waru Djuriatno; Eka Maulana (Jurnal Mahasiswa TEUB, 2023)
Fuel cell is one of the environmentally friendly renewable energy generators. The fuel cell requires oxygen and hydrogen which act in the membrane so that it can generate electricity. The results of the reaction that occurs in the fuel cell are electricity, heat and water so that it is more environmentally friendly. However, as a generator of renewable electrical energy, fuel cells have several drawbacks, including the need for balanced oxygen and hydrogen pressure, proper working temperature and proper humidity in order to maintain the performance of the fuel cell itself. This fuel cell stack requires optimal humidity in order to maintain the performance of the fuel cell itself. An external humidifier is one of the solutions to keep fuel cell moisture in order to make its performance more efficient. In this study, a humidifier system is applied which utilizes vibrations from an ultrasonic humidifier to convert water into a gas phase and a fan as a medium for transporting water vapor to the fuel cell. Water in the gas phase will mix with the surrounding air which will be absorbed by the open cathode fuel cell. In this system, DHT 22 functions as a moisture detector around the fuel cell as feedback so that the controller can maintain the ambient humidity value.